Prevalencia de infecciones de vías urinarias en gestantes atendidas en el Distrito de Salud 11D01 Loja - Gómez Chamba, Yolanda Anabel (2023)
Urinary tract infections are a common pathology during pregnancy, which has become a public health problem not only nationally but worldwide; a disease that affects the normal development of pregnancy and brings with it gynecological and obstetric complications during gestation, delivery, and neonatal period, so medical staff must monitor risk factors such as age, habits, multiparity, and others. This study analyzed the prevalence of urinary tract infections in pregnant patients attended during 2021 in the operative units that are part of Health District 11D01. We carried out a descriptive type of research work with a quantitative approach, which used as a data collection tool the monthly reports registered in the Health Care Registry Platform, which the Statistics Department of Health District 11D01 Loja provided us from the database, the population that met the inclusion and exclusion criteria we selected; thus, the sample consisted of 671 pregnant women with a diagnosis of urinary tract infection; with a prevalence of 60.45%; characterized socio-demographically, determining that most of the patients reside in the urban sector, are aged between 20 and 34 years and are of Ecuadorian nationality; in addition, we concluded that the ICD-10 most frequently recorded is unspecified urinary tract infection in pregnancy, on the other hand, we designed actions for the prevention and promotion of diseases during pregnancy.